2013
DOI: 10.1139/bcb-2013-0014
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effects of crocetin in both human adenocarcinoma gastric cancer cells and rat model of gastric cancer

Abstract: This study investigated the therapeutic effect of crocetin, a carotenoid derived from saffron, on gastric adenocarcinoma (AGS) cells and 1-methyl-3-nitro-1-nitrosoguanidine (MNNG)-induced gastric cancer in rats. An MTT assay showed a significant dose- and time-dependent inhibition of AGS cell proliferation as a result of crocetin administration. Flow cytometry and caspases activity assays revealed apoptosis had been induced in these cells; RT-PCR and Western blot analyses revealed the suppression of Bcl-2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 25 publications
1
75
0
1
Order By: Relevance
“…Apoptosis is characterized by morphological changes for instance, cell shrinkage, membrane blebbing, chromatine condensation, DNA fragmentation and loosing organelles position in cytoplasm (Aghbali et al 2013;Galluzzi et al 2007). It has been shown that some plants such as saffron, curcumin and Ginger suppressed carcinogenic progress through induction of apoptosis (Bakhshi et al 2008Bathaie et al 2013). In our study, Berberis extracts have caused main morphological changes in the treated cancer cells (data are not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis is characterized by morphological changes for instance, cell shrinkage, membrane blebbing, chromatine condensation, DNA fragmentation and loosing organelles position in cytoplasm (Aghbali et al 2013;Galluzzi et al 2007). It has been shown that some plants such as saffron, curcumin and Ginger suppressed carcinogenic progress through induction of apoptosis (Bakhshi et al 2008Bathaie et al 2013). In our study, Berberis extracts have caused main morphological changes in the treated cancer cells (data are not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants of herbs may mediate these biological effects by directly reacting with ROS, free radical scavenging or catalytic metals chelating (Kaliora et al 2006;Koncic et al 2010). Furthermore, medicinal plants with antioxidant potential inhibit proliferation of different cancer cells via apoptosis induction (Samarghandian and Shabestari 2013;Bathaie et al 2013;Hoshyar et al 2012Hoshyar et al , 2013. Apoptosis or programmed cell death is an ordered cellular suicide process that occurs in both physiological and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…effects have been reviewed elsewhere (14,23). In this experimental study, we examined and compared, for the first time, the effects of saffron stigmas, petals, and their mixture on body weight, biochemical and hormonal profiles, insulin resistant HOMA, atherosclerosis and atherogenic indices, and oxidative stress parameters on diet induced obesity in rats.…”
Section: Saffron Is a Commonly Used Herb Which Its Medicinalmentioning
confidence: 99%
“…[1,3,[7][8][9][10][11][12][13][14] In parallel, the possible uses of saffron and its active constituents lead to an increasing number of research studies, some of which have drawn some very useful and intriguing results of active ingredients of saffron, especially against malignancies, cardiovascular and Alzheimer's disease. [15][16][17][18][19][20][21][22] In this minireview, we aim to summarize and critically address previous and current evidence regarding the biological/ pharmacological activities of saffron and its active ingredients and their possible therapeutic uses. The history and structural features of saffron constituents are given in the first part of the review, followed by a comprehensive and critical presentation of the published preclinical and clinical studies and review papers on the pharmacology and potential therapeutic applications of saffron and its main active components.…”
Section: Introductionmentioning
confidence: 99%